Proposal of smoothing space: disputes around the “modern Manaus” (Tempo e Argumento, 2016)
AbstractThis article presents a reflection on projects for the so-called area of “Modern Manaus” in the city of Manaus/Amazonas, Brazil, which aim to create activities to define the uses of space as scenarios. This area stands as a space of dispute by various interested parties in the city of Manaus. The focus of this article lies with the changes proposed for the area of Modern Manaus and the issues experienced currently by this spatiality, for it is understood that pressures and class struggles are experienced in the city as a whole and, therefore, highlight the tensions of living in the city. Keywords: Manaus – City; Memories; History; Photos; Oral Sources. Original title: Propondo o alisamento do espaço: disputas em torno da “Manaus moderna”